STIL Endows Oncogenic and Stem-Like Attributes to Colorectal Cancer Plausibly by Shh and Wnt Signaling - Pradhan, Tapas; Kumar, Vikas; Surya H, Evangeline; Krishna, R.; John, Samu; Jissa, V. T.; Anjana, S.; Chandramohan, K.; Nair, S. Asha (Frontiers in Oncology, 2021)
Discovery of potent genes regulating tumorigenesis and drug resistance is of high clinical importance. STIL is an oncogene, however, its molecular insights and role in colorectal oncogenesis are unknown. In this study, we have explored the role of STIL in tumorigenesis and studied its molecular targets in colorectal cancer (CRC). STIL silencing reduced proliferation and tumor growth in CRC. Further, STIL was found to regulate stemness markers CD133 & CD44 and drug-resistant markers Thymidylate synthase, ABCB1 & ABCG2 both in in-vitro and in-vivo CRC models. In addition, overexpression of STIL mRNA was found to be associated with reduced disease-free survival in CRC cases. To our surprise, we observed an Shh independent regulation of stemness and drug-resistant genes mediated by STIL. Interestingly, we found an Shh independent regulation of β-catenin mediated by STIL via p-AKT, which partially answers Shh independent regulatory mechanism of CSC markers by STIL. Our study suggests an instrumental role of STIL in the molecular manifestation of CRC and progression.